Spitz and Fisher's medicolegal investigation of death guidelines for the application of pathology to crime investigation - Spitz, Werner U., 1926-; Spitz, Daniel J; Fisher, Russell S. 1916- (Charles C. Thomas Publisher, 2006)
MEDICOLEGAL INVESTIGATION OF DEATH, known as the 'bible' of forensic pathology to pathologists around the world, has withstood the test of time, recently celebrating its twentieth year of publication. Totally rewritten and updated throughout, the text is oriented to forensic pathologists, criminal investigators, and attorneys. It embraces all aspects of the pathology of trauma as it is witnessed daily by law enforcement officers, interpreted by pathologists of varying experience and expertise in forensic pathology, and used by lawyers involved in the prosecution and defense in criminal cases as well as those engaged in civil litigation. This authoritative and complete textbook is written by some of the most respected experts in the United States. The book continues to use a simple and practical approach in keeping with the tradition established by the previous editions. It avoids technical terminology, where possible, in compliance with the aim of addressing not only physicians but all parties with an interest in the study of injury patterns and the practice of pathology as it relates to the law. A large amount of new information and abundant material not previously covered are included in this volume. The many new illustrations, diagrams and sketches showing patterns and mechanisms of injury as well as an inclusive index render this book unique.